Public Libraries Help Patrons of Color to Bridge the Digital Divide, but Barriers Remain - MacKenzie, Kimberly (Evidence Based Library and Information Practice, 2021)
A Review of: Pun, R. (2021). Understanding the roles of public libraries and digital exclusion through critical race theory: An exploratory study of people of color in California affected by the digital divide and the pandemic. Urban Library Journal, 26(2). https://academicworks.cuny.edu/ulj/vol26/iss2/1/ Abstract Objective – This study explored the role of the public library in the support of patrons of color who experience digital exclusion. Design – In-person and telephone interviews, grounded theory, and critical race theory. Setting – Public libraries in California. Subjects – Persons of color who were active public library technology resource users due to experiencing the digital divide. Methods – In-person, 60- to 90-minute interviews were conducted with participants referred to the author by public librarians at select libraries in California. Sixteen open-ended questions were asked, relating to demographics, access to technology at home, library technology access and use, technology skills, and thoughts on how libraries could change or improve technology services. A 20- to 30-minute follow-up interview was conducted during the phase of the Covid-19 pandemic when public libraries were closed. Interview transcripts were analyzed by the author, who created a codebook of common themes. Responses were analyzed through the lens of grounded theory and critical race theory. Main Results – Nine participants were recruited; six consented to the first interview and two of the six consented to the second interview. Four of the participants self-reported as Asian, one as Black/African American, and one as Hispanic/Latino American. None of the participants had internet access in their homes, though some reported having laptops or inconsistent cellular service. Common uses of library technology included job search activities (resume building, job searching, applications); schoolwork; research and skill development; and legal or housing form finding. Leisure activities including social media and YouTube were also mentioned. Access limitations included inconvenient library hours, particularly for those attending college or holding a job with daytime hours, and physical distance from the library. A common complaint was the time limit on computer access set by the library; “the concept of time” was mentioned “over 70 times collectively by all participants” (p. 14). Language was another barrier to access, mentioned by three of the participants. Most reported being more likely to ask for help from a library staff person who shared their language or had a similar background. Participants also reported wishing more technology workshops were offered, especially workshops in languages other than English. The two participants who took part in the second interview “expressed frustration and sadness” about the lack of library access during the Covid-19 pandemic (p. 16). One participant reported having to get internet access at her home for her children to attend school. The second participant expressed her difficulty in conducting research or printing information with only the small screen of her phone to provide access. Conclusion – Library patrons of color living within the digital divide make use of public library technology but experience multiple barriers. Libraries can alleviate these barriers by examining their hours, policies, and staffing models to be more accessible to patrons of color lacking internet access at home.